Single-event-latchup detection based on machine learning - Qin, Zhiao (Nanyang Technological University, 2023)
In space, the radiation effects on electronic devices may lead to anomalies referred to as Single-Event-Effects (SEEs). The Single-Event-Latchup (SEL) is a type of SEE arising from heavy-ions striking semiconductor devices, and is characterized as a high-current abnormality. This abnormality causes the loss of functionality and may result in permanent device damage. In addition to SELs, there are micro-SELs where the induced current (abnormality) is lower and more localized than SELs. They are consequently more difficult to detect as their characteristics are often masked by the normal operating current of the semiconductor device.